The influence of civic literacy, civic understanding, and civic tech on students’ digital political participation - Cahyaningrum, Andhini Sepyana; Heru Prasetiyo, Wibowo (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
This study aims to analyze the influence of civic literacy, civic understanding, and civic technology (civic tech) on students’ digital political participation. The research employed a quantitative approach with an explanatory research design. Data were collected through an online survey from students Universitas Muhammadiyah Surakarta, selected using proportional stratified random sampling. The research instrument consisted of a five-point Likert scale. The validity of the instrument was tested using the Pearson Product-Moment correlation, while reliability was measured using Cronbach’s Alpha. Data were analyzed using multiple linear regression, including partial (t) tests, simultaneous (F) tests, and the coefficient of determination (R²). The findings show that civic literacy and civic technology has a positive and significant effect on students’ digital political participation, whereas civic understanding have positive but statistically insignificant effects. These findings emphasize the critical role of civic technology as a behavioral control factor (perceived behavioral control) within the framework of the Theory of Planned Behavior (TPB). This study expands the application of TPB in the context of digital civic education and underscores the importance of integrating civic literacy, citizenship values, and civic tech competence to foster active and responsible digital citizens.